1988
DOI: 10.1002/nur.4770110307
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the performances of baccalaureate, associate degree, and diploma nurses: A meta‐analysis

Abstract: The findings of 139 studies of nurses educated in one of three basic nursing education programs (associate degree, diploma, and baccalaureate degree) were synthesized using meta-analysis. The results indicated significant differences between professional (BSN) and technical (AD and diploma) nurses on measures of nurse performance. Measures resulting in larger effects for professional nurses included communication skills, knowledge, problem-solving, and professional role. No differences resulted from studies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…Two research studies by Aiken and colleagues 7,8 demonstrated improved patient outcomes when care was provided by nurses educated at the baccalaureate level or higher. The results of these studies substantiate earlier research that suggested baccalaureate‐prepared nurses are more likely to exhibit increased knowledge of professional role, problem‐solving abilities, and communication, three skills of increasing importance in today's complex health care environment 9 …”
Section: Introductionsupporting
confidence: 83%
“…Two research studies by Aiken and colleagues 7,8 demonstrated improved patient outcomes when care was provided by nurses educated at the baccalaureate level or higher. The results of these studies substantiate earlier research that suggested baccalaureate‐prepared nurses are more likely to exhibit increased knowledge of professional role, problem‐solving abilities, and communication, three skills of increasing importance in today's complex health care environment 9 …”
Section: Introductionsupporting
confidence: 83%
“…Control variables: Because educational level (Johnson, 1988) and years of work experience (McCloskey & McCain, 1988) have been associated with more professional nursing practice, these variables were added to the model as control variables. No study has examined specialty certification's effect on practice behaviors, although a recent study has suggested that "certification may give nurses the means or opportunity to practice in a manner likely to improve outcomes" (Cary, 2001, p. 49).…”
Section: Variables and Instrumentsmentioning
confidence: 99%
“…Such findings are not unexpected, given that a meta‐analysis of 139 studies concluded that university‐prepared nurses score higher than diploma‐prepared nurses on a range of indicators, including knowledge, communication, problem‐solving, and teaching skills (Johnson, ). Similar studies showed that degree‐prepared nurses develop additional competencies on topics such as health policy, leadership, system thinking, funding, quality improvement (IOM, ) and substantially higher levels of research skills that, in turn, support evidence‐informed practices (Kovner, Brewer, Yingrengreung, & Fairchild, ).…”
Section: Resultsmentioning
confidence: 97%